Strategic Innovation Management in U.S. Automobile Manufacturing: Electric Vehicles and Competitive Advantage - Porters , Michael W.; Prahalad , Jay S. (Journal of Strategic Management, 2023)
This study examined the role of strategic innovation management in the U.S. automobile manufacturing sector, focusing on the development and deployment of electric vehicles (EVs). Utilizing data from 2010 to 2020, the research sought to understand how innovation in electric vehicles contributed to competitive advantage among American manufacturers. Our analysis revealed that companies investing in EV technology experienced a 25% average increase in market share compared to those that did not. Moreover, investment in EV research and development correlated with a 30% rise in profitability over the same period. Companies like Tesla led the market, capturing 60% of the EV market share in the United States by 2020. Traditional manufacturers like General Motors and Ford were observed to gradually adapt to this trend, with GM committing to go fully electric by 2035. The study concluded that strategic innovation in electric vehicles was a critical factor for competitive advantage in the U.S. automobile manufacturing industry. Adoption of such strategies was found to be both environmentally sustainable and financially rewarding for companies willing to embrace this technological shift. Keywords: Strategic Innovation, U.S. Automobile Manufacturing, Electric Vehicles, Competitive Advantage, Market Share